Model Pembelajaran Children Learning In Science (Clis): Studi Efektifitas Terhadap Hasil Belajar IPA - Nasrah Nasrah; Nurfadilah Islami (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to determine the description and effectiveness of the application of the Children Learning In Science learning model in science subjects on energy materials for third grade students of SD Negeri 200 Bulue, Marioriawa District, Soppeng Regency. This research approach is a quantitative approach with a quasi-experimental research design in the form of Nonequivalent Control Group Design. The population of this research is the third grade students of SD Negeri 200 Bulue. The sample is 43 students. The research instruments used were tests, observation sheets, and documentation, while the data collection techniques in this study used interviews, observations, documentation and science learning tests. The data analysis used is descriptive data analysis and inferential data analysis. The results of this study indicate that the activity of students in the experimental class is very effective with a percentage of 90%, in the control class it is quite effective with a percentage of 57%. The results of the Independent Sample T-Test at a significance level of 5% obtained a significant value (2-tailed) < (0.003 < 0.05). Based on these results, it can be concluded that it is effective.